Strategi Penguatan Kinerja Umkm Melalui Peran Optimalisasi Financial Teknologi (FINTECH) - Ika Yustina Rahmawati; Wida Purwidianti; Tri Septin Muji Rahayu; Retno Dwiyanti; Alfalisyado Alfalisyado (Prisani Cendekia, 2023)
This service activity is carried out for UMKM players in the Regency. Banyumas. Based on the survey results, there are two general issues related to empowering MSMEs in Banyumas, namely: alternative access to capital/funds and a lack of capacity for financial management skills among MSME actors. This activity aims to convey insights regarding alternative micro business financing (MSMEs) outside of bank finance and provide insight into Islamic financial literacy. Against this background, follow-up activities on Fintech and Islamic financial literacy were held. Fast-growing fintech will help achieve the three main objectives of the Indonesian financial services sector master plan. (1) Contribution, encouraging accelerated growth of the national economy through optimizing functions in the financial services sector, (2) Resilience, sustainable development driven by good management of financial system stability; (3) Inclusive, namely providing a way of convenience in finance with the aim of improving people's lives for the better in the future. Furthermore, financial literacy is carried out with sharia financial literacy training to provide insight into knowledge, abilities and beliefs that influence attitudes and behavior to improve the quality of decision-making and financial management in achieving a better level of life, develop materials on how to optimize the financing of production activities and direct MSME actors to always operate in accordance with sharia principles.